hUCMSCs Regulate Bile Acid Metabolism to Prevent Heart Failure–Induced Intestinal Injury by Inhibiting the Activation of the STAT3/NF‐κB/MAPK Signaling Pathway via TGR5 - Zetian Wang; Wei Luo; Qing Wang; Chunzheng Liu; Yanshan Gong; Baitian Li; Xuejiao Zeng; Jiaqi Lin; Zehua Su; Xin Li; Yongze Yu; Zhongmin Liu; et al. (Food Frontiers)
ABSTRACT The protective effects of human umbilical cord mesenchymal stem cells (hUCMSCs) on heart failure (HF)‐induced intestinal injury have not been fully understood. Flow cytometry and immunofluorescence analysis revealed that hUCMSCs renewed themselves, grew, and transformed into various cell types. Meanwhile, hUCMSCs safeguarded against intestinal damage, regulated imbalances in the intestinal flora and bile acid metabolism, and enhanced the levels of hyodeoxycholic acid (HDCA) in pigs with HF. HDCA protected against HF‐induced intestinal injury in mice through Takeda G protein–coupled receptor 5 (TGR5). Protein analysis showed that HDCA exerted protective effects on the intestines via the signal transducer and activator of transcription 3 (STAT3)/nuclear factor kappa B (NF‐κB)/mitogen‐activated protein kinase (MAPK) signaling pathway. Mouse experiments revealed that HDCA bound to TGR5 to inhibit MAPK and NF‐κB signaling pathway activation, which relies on the STAT3 signaling pathway. Moreover, hUCMSCs protected against intestinal injury in the pig model of HF by suppressing the activation of the STAT3/NF‐κB/MAPK signaling pathway via TGR5.